Effect of Dedhuwa (Esomus danricus), Mara (Amblypharyngodon mola) and Pothi (Puntius sophore) on Carp Production in Chitwan, Nepal - Gupta, M.C.; Rai, S. (Our Nature, 2012)
In order to assess the effect of adding Dedhuwa (Esomus danricus), Mara (Amblyparyngodon mola) and Pothi (Puntius sophore) on Carp production, an experiment was carried out in farmers’ pond in Chitwan. The experiment included four treatments in triplicates: T1, (Carp: Silver carp, Hypophthalmychthys molitrix, Bighead carp, Aristichthys nobilis, Rohu, Labeo rohita and Mrigal, Cirrhinus mrigala), T2 (Carp+Dedhuwa), T3 (Carp+Mara), and T4 (Carp+Pothi). Fish were fed on dough of rice bran and mustard oil cake (1:1) at the rate of 3% of body weight. Results showed that Dedhuwa, Mara and Pothi did not differ significantly (P>0.05) in terms of production. Production of Silver carp and Bighead carp was found significantly higher (P<0.05) in T3 and T4 than control indicating no niche overlapping among these fish. Based on total production and profit T4 appeared to be best. DOI: http://dx.doi.org/10.3126/on.v9i1.5741